Exploring Relationships Between Anthropometry, Body Composition, Maturation, and Selection for Competition: A Study in Youth Soccer Players - Clemente, Filipe Manuel; Clark, Cain C. T.; Leão, César; Silva, Ana Filipa; Lima, Ricardo; Sarmento, Hugo; Figueiredo, António J.; Rosemann, Thomas; Knechtle, Beat (Frontiers in Physiology, 2021)
PURPOSE: The purpose of this study was to analyze variations of selection for competition between late and early mature players and test the relationships between anthropometry, body composition, maturation and selection for the competition. METHOD: Seventy-nine youth soccer players from under-11 to under-14 participated in this study, over six months. Body composition and maturity offset were estimated based on anthropometric data collected. Participants were also monitored for their number of matches as starters and time of play accrued in minutes. RESULTS: Minutes played had large correlation coefficients with maturity offset (r=0.58), and leg length & sitting height interaction (r=0.56). Multiple linear regression explained 35% of the variation in minutes played (p<0.001, R2=0.41, R2adjusted=0.35, RMSE=334.8), but only 12% of the variation in matches as a starter (p=0.04, R2=0.21, R2adjusted=0.12, RMSE=5.47), between above and below the median of the maturity offset was accounted for, respectively. CONCLUSIONS: although maturation may play a role in the minutes of play accrued and matches as starters in young, it is not necessarily determining. A significant amount of the variation in the minutes of play accrued of players can be accounted for when considering body composition and anthropometric data.